2020
DOI: 10.3390/biom10020190
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Activity of Pleurotus sajor-caju (Fr.) Sing β-1,3-Glucanoligosaccharide (Ps-GOS) on Proliferation, Differentiation, and Mineralization of MC3T3-E1 Cells through the Involvement of BMP-2/Runx2/MAPK/Wnt/β-Catenin Signaling Pathway

Abstract: Osteoporosis is a leading world health problem that results from an imbalance between bone formation and bone resorption. β-glucans has been extensively reported to exhibit a wide range of biological activities, including antiosteoporosis both in vitro and in vivo. However, the molecular mechanisms responsible for β-glucan-mediated bone formation in osteoblasts have not yet been investigated. The oyster mushroom Pleurotus sajor-caju produces abundant amounts of an insoluble β-glucan, which is rendered soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Inactivation of the Wnt/β‐Catenin pathway can inhibit valve calcification, 17 and Runx‐2 acts coordinately with components of the Wnt/β‐catenin signalling pathway to enhance gene expression of both osteogenic bone markers and mineralization. 18 Hence, the levels of Wnt/β‐catenin pathway‐related proteins in tissues and cells were detected. The Wnt/β‐catenin pathway was activated in CAVD group compared with the blank group, and EV treatment inhibited the Wnt/β‐catenin pathway; knockdown of miR‐30b attenuated the inhibitory effect of TC‐EVs on the Wnt/β‐catenin pathway ( Figure 6 B ).…”
Section: Resultsmentioning
confidence: 99%
“…Inactivation of the Wnt/β‐Catenin pathway can inhibit valve calcification, 17 and Runx‐2 acts coordinately with components of the Wnt/β‐catenin signalling pathway to enhance gene expression of both osteogenic bone markers and mineralization. 18 Hence, the levels of Wnt/β‐catenin pathway‐related proteins in tissues and cells were detected. The Wnt/β‐catenin pathway was activated in CAVD group compared with the blank group, and EV treatment inhibited the Wnt/β‐catenin pathway; knockdown of miR‐30b attenuated the inhibitory effect of TC‐EVs on the Wnt/β‐catenin pathway ( Figure 6 B ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study suggested that Pleurotus sajor-caju (Fr.) Sing β-1,3-Glucanoligosaccharide ( Ps -GOS) promotes bone formation by inducing osteoblast proliferation, differentiation, and mineralization via the MAPK pathway [ 56 ]. Our study reported that BZYQD in each dose group strengthened the p-ERK1/2/ERK1/2 and p-P38 MAPK/P38 MAPK ratios in the femoral tissue of OPF rats.…”
Section: Discussionmentioning
confidence: 99%
“…The laser irradiation at 5.0 J/cm 2 upregulated DSPP and DMP1 expression at D7 and D14, demonstrating that DMP1 and DSPP expression are essential in the late stages of odontogenesis following PBM application. RUNX2 exerts different effects depending on the stages of osteogenesis and functions at the intersection of many other osteo/odontogenic differentiation-related pathways such as the BMP signaling pathway (Li et al, 2019;Yodthong et al, 2020). RUNX2 expression increased with statistical signi cance at D3, D7 and D14 for all of the three energy uences, with the 5.0 J/cm2 group being the most effective energy intensity with at D14 as a late phenomenon, suggesting a dose-time-dependence response in accordance with the biomineralization results.…”
Section: Discussionmentioning
confidence: 99%